Liberal Arts Digest VOLUME 08 - Tussupbekova, Zh.; Kaliyev, A.; Әмірсейіт, А.; Усенко, Е.; Мырзан, А.; Хурматуллаева, Қ.; Бағайқызы, А.; Abishev, T.; Kizatova, K.; Kopzhassarova, A.; Konussova, K.; Meiramov, A.; et al. (Maqsut Narikbayev University, 2024)
Liberal Arts Digest is a peer-reviewed academic journal established in 2021 by the School of Liberal Arts at Maqsut Narikbayev University. The journal is designed to promote student engagement in scientific inquiry and research by providing an inclusive platform for both undergraduate and graduate students, as well as early-career researchers. Dedicated to the fields of humanities and social sciences, Liberal Arts Digest publishes original research articles, critical reviews, and theoretical reflections. The journal welcomes contributions across a range of topics, including: Philosophy and identity, History of Kazakhstan, Pedagogy and educational practices, Linguistics and language teaching methodologies, Translation studies, Tourism and cultural studies
Keywords: School of Liberal Arts at Maqsut Narikbayev University, Liberal Arts Digest, Philosophy and identity, History of Kazakhstan, Pedagogy and educational practices, Linguistics and language teaching methodologies, Translation studies, Tourism and cultural studies